Pendampingan Pelaksanaan Pembelajaran Efektif Melalui Model Student Centered Learnig di Madrasah Diniyah Al-Mukhlisin Ketawang, Gondang, Nganjuk - Suhartono; Indramawan, Anik (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2025)
Effective learning is a learning process that is active and enjoyable for students to achieve the expected learning objectives. The learning conditions at the assisted partner institutions are still not implemented effectively due to teacher-centered learning, so it is necessary to provide mentoring as a form of Community Service activities that aim to provide mentoring to teachers at Madrasah Diniyah Al-Mukhlisin Ketawang, Gondang, Nganjuk in implementing effective learning through the student-centered learning model. The results of the community service activities showed that the motivation of the assisted subjects was very good in participating in the mentoring activities with a percentage of 100% or all teachers had high motivation in this mentoring activity. Furthermore, the understanding of the mentored material was 10 teachers or 83.33% who understood the mentoring material. The ability of the assisted subjects to practice the student-centered learning model in the learning process was 66.67% or as many as 8 assisted subjects who were able to practice learning with the student centered learning model. The results of this analysis indicate that this community service activity was successful and warrants follow-up with effective implementation of student-centered learning, ensuring students actively participate in the learning process and achieving the desired learning objectives.